Nutrient Enrichment of Artemia salina Using the Bioencapsulation Method with Single Cell Protein Extract from Chlorella Vulgaris - Saputra, Anugerah; Karim, Yusri; Zainuddin; Kuswanto, Hedi (International Journal of Science and Society, 2025)
Single Cell Protein (SCP) is a biotechnological product designed to enhance biomass or extract proteins and lipids from a given material. One of the methods to utilize single-cell protein is bioencapsulation. Bioencapsulation is a nutrient enrichment technique that involves adding specific substances to natural feed to improve its quality and quantity, thus enhancing its overall nutritional value. The single-cell protein used in this study is Chlorella vulgaris (C. vulgaris), while the bioencapsulation material or observed subject is Artemia salina (A. salina). This study aims to analyze the nutritional content based on the retention or absorption capacity of A. salina using the SCP bioencapsulation method from C. vulgaris and to determine the optimal SCP dosage for bioencapsulation in A. salina. The tested dosages in this study were 100 mg/L, 200 mg/L, 300 mg/L, and 0 mg/L (without SCP administration as a control). The results showed that the SCP retention value in A. salina was significantly different (P<0.05) across the tested dosage treatments. The highest retention value was observed at a dosage of 300 mg/L, with the highest retention of soluble protein and fat recorded at 85.65% and 0.27%, respectively. However, the overall results indicate that as the administered SCP dosage increases, the retention or absorption of SCP nutrients in A. salina also increases.